Feature selection for linear SVMs under uncertain data: Robust optimization based on difference of convex functions algorithms - Le Thi, Hoai An; Vo, Xuan Thanh; Pham Dinh, Tao (Neural networks, 2014)
In this paper, we consider the problem of feature selection for linear SVMs on uncertain data that is inherently prevalent in almost all datasets. Using principles of Robust Optimization, we propose robust schemes to handle data with ellipsoidal model and box model of uncertainty. The difficulty in treating ℓ0-norm in feature selection problem is overcome by using appropriate approximations and Difference of Convex functions (DC) programming and DC Algorithms (DCA). The computational results show that the proposed robust optimization approaches are superior than a traditional approach in immunizing perturbation of the data.